Analisis Metode Bercerita Berbasis Digital untuk Meningkatkan minat Baca pada Anak Usia Dini - Fitriyani, Rini; Rahmawati, Elsi; Indah, Risma Permata Sari (Jurnal Kridatama Sains dan Teknologi, 2025)
Digital-based storytelling methods make it easier for teachers and parents to increase interest in reading in early childhood. so this research was conducted to analyze digital-based storytelling methods to increase interest in reading in early childhood in Samarinda city. With a descriptive qualitative approach, data were obtained through in-depth interviews and observations of kindergarten and KB teachers and parents. By using digital in the process of storytelling activities to children so that children do not feel bored and saturated. Digital-based storytelling methods are key for teachers and parents in every learning activity to increase understanding and attract children's interest in reading. The results of the analysis show that there is a positive relationship between digital-based storytelling methods and children's reading interest, being fun for teachers and parents, supporting children's learning participation in reading interest. However, this study also identified challenges in the digital storytelling method, such as teachers who are still unfamiliar with the use of technology and parents' low economic status. Teachers and parents stated that this digital storytelling method can help and provide adequate support to be an attraction in children's interest in reading. This study concludes that although digital storytelling has the potential to increase children's interest in reading, digital storytelling has the potential to increase children's interest in reading